2019
DOI: 10.1007/s10796-019-09903-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Gap between Technology and the Environmental Sustainability of European Cities

Abstract: The growth of cities' population increased the interest in the opportunities and challenges that Information and Communication Technology (ICT) have on carbon footprint reduction, which fosters their environmental sustainability. Using Principal Component Analysis (PCA), six ICT-related variables from European Union (EU) cities were combined into a single twodimensional ICT index. Then, through cluster analysis, cities were clustered into four groups based on the ICT index and Carbon dioxide (CO 2 ) emissions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 83 publications
0
36
0
Order By: Relevance
“…During the past decades, the digital revolution has dramatically changed the societies and economies and offered new possibilities and pathways that significantly altered the human lives. Previous studies suggest that digital transformation might be a significant driver to achieve sustainability (Maffei et al 2019), and has generated entirely new mechanisms to maintain and promote natural resources, national wealth, and well-being (Akande et al 2019). Accordingly, several IS researchers suggest that nations should set programs and undertake initiatives towards digitalisation in order to achieve sustainability objectives (Bednar and Welch 2019;Kar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, the digital revolution has dramatically changed the societies and economies and offered new possibilities and pathways that significantly altered the human lives. Previous studies suggest that digital transformation might be a significant driver to achieve sustainability (Maffei et al 2019), and has generated entirely new mechanisms to maintain and promote natural resources, national wealth, and well-being (Akande et al 2019). Accordingly, several IS researchers suggest that nations should set programs and undertake initiatives towards digitalisation in order to achieve sustainability objectives (Bednar and Welch 2019;Kar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The digital revolution has radically transformed economies and help societies to develop new mechanisms for human wellbeing, national wealth, natural resources, and sustainability. 60 , 61 Drawing on the complexity theory, Delgosha et al 33 argued that ICT usage, adoption, capabilities, and infrastructures encourage countries to achieve sustainable competitiveness without compromising social and natural capital. Using a global panel data of 107 countries, Laidroo and Avarmaa 62 revealed that FinTech establishment intensity is stronger in countries with greater ICT readiness and service clusters.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In the literature, it is possible to find "Smart City" analogous concepts referred to in relatively different ways. Several different wordings appear, with "Green City", "Sustainable City", and "Intelligent City" being the most common [10,18,[24][25][26][27][28]. Using the "Web of Science" search engine with the string: AK = (("smart" OR "green" OR "sustainable" OR "intelligent") AND ("city" OR "cities"))], it was possible to find 8,518 publications with the referred keywords since 1992.…”
Section: Literature Reviewmentioning
confidence: 99%